Peran Guru dalam Kegiatan Pembelajaran dari Rumah pada Masa Pandemi Covid-19 di SD Islam Sari Bumi Sidoarjo - Alfiyatul Maghfiroh Lil Ummah; Septi Budi Sartika (Jurnal Bidang Pendidikan Dasar, 2021)
The research aims to describe the role of teachers and constraints in learning activities from home during the covid-19 pandemic at SD Islam Sari Bumi Sidoarjo. The focus of teacher role research includes pedagogical competencies, namely the ability of teachers to manage classes with 3 indicators namely planning, implementation, and assessment of learning. The research method uses a qualitative approach to phenomenological types. Research instruments use questionnaires, interviews, and documentation. Data analysis techniques using the Miles and Huberman models include data reduction, data display, verification and conclusions. The results showed that the role of teachers in learning activities from home during the covid-19 pandemic at SD Islam Sari Bumi Sidoarjo on planning indicators, and learning assessments have been achieved. As for the obstacles faced by teachers in learning activities from home during the covid-19 pandemic at SD Islam Sari Bumi Sidoarjo is a network / signal that is not good and parents who pay less attention to the child's duties because they are busy working. Further research is expected to uncover the facts through different sources, because the learning activities are done from home then the checking of the validity of the role of the teacher can be done to the student or the parents, thus the analysis and conclusion will be in-depth.